A comparative transcriptome and proteomics study of post‐partum ovarian cycle arrest in yaks (Bos grunniens). Issue 3 (5th December 2021) - Huo, Shengdong; Chen, Zhou; Li, Shuyuan; Wang, Jine; Ma, Junyuan; Yang, Yanmei; Zhaxi, Yingpai; Zhao, Yongqing; Zhang, Derong; Long, Ruijun
Abstract: Post‐partum ovarian cycle arrest is the main factor affecting yak reproductive efficiency. There are few reports regarding the molecular regulatory mechanism of post‐partum oestrus at transcriptome and proteome levels in yaks. Our previous studies focussed on the ovaries of yaks with post‐partum ovarian cycle arrest and post‐partum oestrus yaks. In this study, RNA sequencing transcriptomic study was combined with quantitative proteomic analyses to identify post‐partum ovarian cycle‐related genes and proteins. Consequently, 1, 149 genes and 24 proteins were found to be up‐ or downregulated during post‐partum oestrus. The analysis of differentially regulated genes identified three gene or protein pairs that were synchronously upregulated and no gene or protein pairs that were synchronously downregulated, suggesting that these upregulated genes may regulate the post‐partum ovarian cycle. The functional classification of these differentially expressed genes and proteins indicated their connection with the oocyte meiosis, the oestrogen signalling pathway, the progesterone‐mediated oocyte maturation and the gonadotrophin‐releasing hormone (GnRH) signalling pathway. In this study, a total of six genes and two proteins involved in the oocyte meiosis, the oestrogen signalling pathway, the progesterone‐mediated oocyte maturation and the GnRH signalling pathway were identified. The CSNK1A1, M91_09723, M91_11326, M91_21439, M91_19073, SHC2, Atf6b, M91_03062, HSPCA and calmodulin could regulate oestrus, respectively, in the post‐partum so as to control the anoestrus status.